An integrated approach to planning for sustainable land and town as commons - Stefano Aragona (European Regional Science Association (ERSA), 2014)
The starting point consists in considering city as common good as a whole characterized by a number of physical and social local resources that are not reproducible ones. Remembering that the mission of the modern town planners, from the Athena Chart 1931, is the wellbeing of the inhabitants. Renewable resources and interactive communications may help do design a better urbanization processes. But all that must be done having as goal to construct local communities and not only to reinforce individual power. As the European Union says for/in Horizon 2020 the scope has to build "Smart Cities" that are referred not only to technological aspects but they also constituted by an inclusive, social sustainable environment. Flows of energy and flows of communications characterize the contemporaneous city: the immaterial city (Aragona, 1993, 2000). Town planners have to face with this phenomenon but it is not easy because they are for the most, especially in some nation (e.g. Italy), not educated to do that. It requires to manage the networks of services - not visible service and product (some years ago called often "value added service") - beside the physical, built, town that means its spatial, economical structure? and the functional one that is changing (partly or totally) because the reasons before said. This philosophy regards also the energy and all the natural elements (water, wind, soil) contributing to increase the quality life. It seems that, for the most, in many countries town planners accept these changes without trying to address them. It seems that the countries where city as common good is less felt (e.g. many of the Mediterranean nations) these changes for bettering wellbeing and social sustainability are not caught or left to the "free market" alone? while Sustainable Copenhagen is one representative example of what can be done. All that is very related to the accessibility of information of people, technicians, administrative employees, politicians. Important is the formation of a "cultured technology" for avoiding technocratic "solutions" (Del Nord, 1991). All that is a relevant chance because inhabitants become citizens i.e. cum-cives of the polis: outcome of the art of managing the city. References Aragona S. (1993) La città virtuale. Trasformazioni urbane e nuove tecnologie dell'informazione, Gangemi, Roma. Aragona S. (2000) Ambiente urbano e innovazione. La città globale tra identità locale e sostenibilità, Gangemi, Roma. Cacciari M. (1991) "Aut civitas, aut polis" in (a cura di) Mucci E., Rizzoli P., L'immaginario tecnologico metropolitano, F.Angeli, Milano. Del Nord R. (1991) "Introduzione" in (a cura di) Mucci E., Rizzoli P., L'immaginario op.cit? Ue, (2012) Smart Cities e Communities, Asse II del Programma (azioni integrate per lo sviluppo sostenibile e lo sviluppo della società dell'informazione) e progetti di "innovazione sociale" Asse III www.Copenhagen.TheSustainableCity.it
Keywords: 330; urban sustainability; integrated planning; commons; Q01 Sustainable Development